Convergence of the Born and inverse Born series for electromagnetic scattering. Issue 10 (27th July 2017) - Kilgore, Kimberly; Moskow, Shari; Schotland, John C.
Abstract : We consider the Born and Inverse Born series that arise in the theory of electromagnetic scattering and related inverse problems. We establish sufficient conditions for convergence of both series.